The Effectiveness of Prezi Video Media in Developing Religious and Moral Values Among Early Childhood Learners - Trivena Datubua Toboe; Nurhayati Nurhayati; Hesti Putri Setianingsi; Andi Agusniatih (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
The development of religious and moral values is a crucial foundation in shaping the character of early childhood learners. This study aims to evaluate the effectiveness of Prezi Video media in fostering religious and moral development in Group B children. Employing an experimental design with a quantitative approach, the study focused on three core aspects: identifying religions and places of worship, maintaining personal hygiene, and performing prayers according to one's faith. A total of 15 children from Tut Wuri Handayani Kindergarten participated in the study. Data were collected through pre-test and post-test observations conducted before and after the implementation of Prezi Video media. The findings revealed a significant improvement across all three aspects, with most children progressing from the "Emerging Development" category to "Developed as Expected" and "Very Well Developed" after the intervention. These results indicate that Prezi Video media is an effective tool for enhancing early childhood understanding and application of religious and moral values.